DESAIN BERBAGAI RANGKAIAN LISTRIK SEDERHANA DENGAN MEMANFAATKAN APLIKASI DROID TESLA V6.21 - Kezia Noviani Anou; Zakaria Victor Kareth (JURNAL PENGABDIAN PAPUA, 2022)
The target of the science and technology application service activity is given to students of SMA N 3 Sentani. The purpose of this activity is to carry out the tri dharma of higher education and provide mentoring to students in the use of learning applications. The application used is the Droid Tesla V6.21. This application helps students to more easily recognize electronic components and makes it easier for students to design electronic circuits such as assembling series and parallel electrical circuits. This activity has been carried out using lecture and practice methods as well as giving Pre Test and Post Test. The result of this activity is that students recognize and are able to run new applications as well as products in the form of series and parallel electrical circuits that are made based on the circuit design in the application.Keywords: technology application; The Droid Tesla V6.21; design electronic